EDUKASI DAN PELATIHAN PEMBUATAN MINUMAN ISOTONIK DARI AIR KELAPA - Wima Anggitasari (LPPM Universitas dr. Soebandi, 2025)
Sports are one of the activities that aim to maintain physical fitness and restore physical and mental health. One of the problems that often arises when someone does sports is fatigue. Fatigue is a decrease in the quality and quantity of work or sports activities caused by or resulting from doing certain work or sports. One way to overcome this is to use isotonic drinks. Coconut water is one source of isotonic drinks. The purpose of implementing this activity is to increase knowledge related to the use of electrolyte drinks and improve participants' skills in making electrolyte drinks from natural ingredients, namely coconut water. The method of implementing this activity begins with a pretest, providing material with lectures, discussions, and Q&A, demonstrations of how to make electrolyte drinks from coconut water, and post-tests. The results of the activity evaluation showed that education was able to increase knowledge related to the use of isotonic drinks and the skills of making isotonic drinks in members of the Sekolah Lansia Tangguh (SELANTANG). The conclusion of this activity is that education and training can improve the health status of the community, especially in SELANTANG.